Employee Incentives, Job Satisfaction and Turnover Intention in the Hospitality Industry in Portugal - de Moura, L.; Duarte, A.P. (International Conference on Applied Business and Management (ICABM2022), 2022)
Hospitality companies are highly dependent on the quality of their employees to develop and deliver a competitive tourism offering. As a customer service-centered sector, hospitality businesses need to focus on employee engagement to be successful. However, attracting and retaining employees has been a challenge in this sector (Coelho & Bartolomeu, 2021; Ribeiro et al., 2020; Park & Min, 2020). The sector is known to be demanding (e.g., working hours, schedules, physical abilities), but poorly competitive in terms of the work conditions offered to its workers (e.g., low salaries, precarious employments contracts, limited career development opportunities; Hinkin & Tracey, 2000; Davidson & Wang, 2011). Previous literature has tried to determine the main reasons for hospitality employees to leave their jobs and the measures companies might implement to prevent this situation. Several factors were identified, including the (poor) incentives companies offer to employees in exchange for their work and job (dis)satisfaction (Andrade et al., 2020; Park & Min, 2020; Tan et al., 2020). Focusing in the Portuguese hospitality sector, the present study had two-fold aims. First, it sought to identify the incentives (financial and non-financial) that employees value the most and compare them with the incentives provided by their companies. Second, it aimed to examine the effect of provided incentives on employees’ turnover intention, within the context of a theoretical model that includes job satisfaction as a mediating variable.